ONLINE SHOP VOCABULARY ON INSTAGRAM SOCIAL MEDIA AND CONTRIBUTION TO INDONESIAN LANGUAGE LEARNING - Rahmawati; Andi Sukri Syamsuri; Muhammad Akhir (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the vocabulary used in online shop activities on Instagram social media and examine its contribution to Indonesian language learning. Through a qualitative-descriptive approach, data is collected from uploads and product descriptions on several popular online shop accounts . The results of the analysis show that the vocabulary used reflects a mixture of non-standard Indonesian, foreign absorption (especially English), abbreviations, and popular terms (slang) that are developing in online communities. The collection of data is sourced from 5 (five) Online Shops, namely @omorfoo_shop, @bunoshopp28, @sental.kaos, @akavi.id, and @citracosmetic_id. The contribution to Indonesian learning lies in the potential use of authentic context from social media as teaching materials, especially in learning language diversity, vocabulary development, and language attitudes.